2020
DOI: 10.1111/pbi.13400
|View full text |Cite
|
Sign up to set email alerts
|

A fungal effector and a rice NLR protein have antagonistic effects on a Bowman–Birk trypsin inhibitor

Abstract: Bowman-Birk trypsin inhibitors (BBIs) play important roles in animal and plant immunity, but how these protease inhibitors are involved in the immune system remains unclear. Here, we show that the rice (Oryza sativa) BBI protein APIP4 is a common target of a fungal effector and an NLR receptor for innate immunity. APIP4 exhibited trypsin inhibitor activity in vitro and in vivo. Knockout of APIP4 in rice enhanced susceptibility, and overexpression of APIP4 increased resistance to the fungal pathogen Magnaporthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…This research reveals that many genes are involved in the defense network of Piz-t-KJ201, consistent with previous observations (Park et al 2012(Park et al , 2016Wang et al 2019;Bai et al 2019;Zhang et al 2020). These genes and TFs identified in the present study were of high biological relevance.…”
Section: Validation Of the Present Study By Comparing Previous Reportssupporting
confidence: 93%
See 2 more Smart Citations
“…This research reveals that many genes are involved in the defense network of Piz-t-KJ201, consistent with previous observations (Park et al 2012(Park et al , 2016Wang et al 2019;Bai et al 2019;Zhang et al 2020). These genes and TFs identified in the present study were of high biological relevance.…”
Section: Validation Of the Present Study By Comparing Previous Reportssupporting
confidence: 93%
“…In our earlier studies, four proteins of a receptor-like protein kinase (gi|59,800,021), a NADP dependent malic enzyme (gi|54,606,800), a putative transaldolase (gi|57, 900,129), and a putative bowman birk trypsin inhibitor (gi|53,792,234), three C3HC4-type Ring finger E3 ubiquitin ligase (APIP2, 6, 10), and a bowman-Birk type bran trypsin inhibitor (APIP4) were confirmed to be involved in Piz-t-KJ201 interaction (Park et al 2012(Park et al , 2016Tian et al 2018;Zhang et al 2020). In the present study, we observed that a receptor-like protein kinase precursor (LOC_Os10g33040), a NADP-dependent malic enzyme (LOC_Os05g09440), a transaldolase (LOC_ Os08g05830), a bowman-Birk type bran trypsin inhibitor precursor (LOC_Os01g03360), and two zinc finger C3HC4 type domain containing protein (LOC_ Os01g20910 and LOC_Os12g04590) were also differentially regulated in Piz-t-KJ201 (Additional Table 2).…”
Section: Validation Of the Present Study By Comparing Previous Reportsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effector is recognized by the cognate host resistance protein Piz-t; however, these two proteins do not interact directly. Zhang et al [220] showed that the rice (Oryza sativa) BBI protein, named APIP4 (AvrPiz-t interacting protein 4), was involved in this interaction and played a positive role in rice immunity. The fungal AvrPiz-t directly targets APIP4 and reduces its inhibitor activity in vivo and in vitro.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Oryzae [26]. One rice BBI, APIP4, interacts at the protein level with both a fungal effector and host NLR receptors as part of the innate immune response, and plants carrying lossof-function mutations in this gene exhibit increased susceptibility to Magnaporthe oryzae [27]. In wheat, genetic mapping studies identi ed putative BBI genes as candidates for seedling resistance to tan spot [28] and Fusarium head blight [29].…”
Section: Introductionmentioning
confidence: 99%